KNOWLEDGE, ATTITUDES, AND PRACTICES OF ADOLESCENTS IN THE CITY OF KINDU TOWARD SICKLE CELL DISEASE - Amisi Masudi Maurice (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2025)
Sickle cell disease is a significant genetic disorder, particularly in sub-Saharan Africa, where it represents a major public health challenge. This study was conducted in Kindu, Maniema Province (DRC), to identify barriers to primary prevention practices among adolescents aged 10 to 19 years. A cross-sectional survey was carried out with 386 adolescents selected through stratified sampling. Data were collected using a structured questionnaire covering knowledge, attitudes, and practices (KAP) regarding sickle cell disease. Descriptive and bivariate analyses were performed to assess KAP levels and explore associations with sociodemographic variables. The results reveal a substantial knowledge gap: only 35% of adolescents were aware of the mode of transmission, and 18% knew about diagnostic tests. Attitudes were predominantly unfavorable: over 80% perceived sickle cell disease as severe but were reluctant to undergo screening due to stigma and insufficient institutional support. Preventive practices were very low, with over 90% never participating in awareness campaigns or sharing information about the disease. These findings confirm that knowledge deficits and sociocultural constraints are the main barriers to effective primary prevention. The study highlights the need to strengthen school-based health education, promote premarital screening, and support community initiatives to enhance adolescents’ engagement in sickle cell disease prevention.